Shock spectrum analysis of multistorey frames - Deepa, B. S.; Nandakumar, C. G. (Journal of Structural Engineering, 2025)
Frames are the most widely used structural system for multistorey buildings, which are three dimensional lattice structures, and are statically indeterminate. Finite element analysis of frames incorporating interaction between foundation and soil, has been studied. Numerical investigations have been carried out on a regular multistorey frame considering depth of fixity at ground level, at characteristic depth of pile and at full depth. Soil structure interaction effects have been studied by considering discrete models for soil. Seismic shock spectrum analysis has been conducted on three types of soil viz., laterite, sand and alluvium. It has been concluded that for shock spectrum analysis using finite element method for multistorey frames with soil structure interaction effects, fixity at characteristic length of pile can be adopted, for laterite and sand; however full length of pile has to be considered for alluvium.